Pengembangan Media Pembelajaran Aplikasi Augmented Reality Berbasis Android Menggunakan Unity untuk Pembelajaran Struktur Atom Senyawa Organik Hidrokarbon - Alfian, Alfian; Hamid, Marsud; Suhardi, Iwan (Indonesian Journal of Educational Studies, 2018)
This study aims to produce a design of augmented reality learning media atomic structure of hydrocarbon organic compounds. This research uses Research and Development (R & D) research methods with prototyping development models, through the needs collection phase, prototyping, system coding, system testing, evaluation, and system use. Software testing focuses on functionality, maintainability, portability, and usability aspects. This research results in (a) Android-based learning media that are mobile, interactive and easy to use so that they can be used by students to study whenever and wherever (b) the results of testing with the criteria "Very Worthy" on aspects of functionality, meet the testing aspects of maintainability; the criteria for "Very Good" on the portability aspect; and the criteria for "Very Good" on testing usability aspects